Russian Economic Report, No. 28, Autumn 2012 : Reinvigorating the Economy - World Bank (World Bank, Washington, DC, 2017)
Early in the year, as the global economy was slowing and the euro area entered a recession, Russia's economy held steady. But now, as 2012 is entering its final quarter, growth is slowing. Just at a time when Russia's output levels have exceeded the pre-crisis peak, the economy is settling onto a lower trajectory, even though oil prices have stayed high. But let us start with the strong points. The economy had a good first half of the year. While growth was stalling in Europe and slowing in other emerging economies, it remained steady in Russia. Key economic indicators were near or at record levels: the current account surplus stayed high and the Central Bank of Russia added to its reserves, helping to bolster market confidence. Capital outflows, long regarded as one of the soft spots of Russia's economy, declined in the second and third quarters of 2012 from the peaks in the previous two quarters. Whereas many countries in Europe are struggling with large public debt and high fiscal deficits, Russia's federal government public debt is close to single digit and the fiscal balance is in surplus. Inflation and unemployment rates declined to their lowest level in two decades. As people's purchasing power improved and more people had jobs, fewer people were in poverty than at any time since the beginning of the economic transition. A challenging external environment and worsening sentiments among businesses and consumers translate into weak growth prospects. Excluding the crisis years of 1998 and 2009, growth in 2012 is set to decline to its lowest rate in a decade and a half. And 2013 is unlikely to look much better. The weak outlook means that strong, three-pronged policy action is essential to reinvigorate the economy. First, economic policies have to ensure stability. The recent tightening in monetary policy was an important step in this direction. Second, Russia has to build buffers against the external volatility. This means replenishing the reserve fund, moving towards inflation targeting and strengthening banking supervision. Finally, the government has to lift the growth potential of the economy. This means raising productivity and competitiveness, diversifying the economy, and improving transport connectivity, as discussed in the last section of this report, in line with its longer-term economic policy goals. Making headway on this agenda will enable Russia to lift growth above 4 percent and more.